The Determinants Of Family Planning Counselors' Stunting Program Objective During Covid-19 A Case Study In East Java - Saeroji Saeroji; Sudeni Sudeni (YCMM, 2022)
Out of the 34 provinces, 12 of them in East Java did not achieve the national stunting prevalence target during the Covid-19 pandemic until 2024. The delay in achieving the work goals of family planning counselors (KB) in the stunting program requires concrete steps to overcome existing obstacles. This study aims to identify the problems that determine the goals of the stunting program for family planning counselors and offer solutions so that they can be used as practical references for family planning counselors. This case study research with descriptive design includes three stages: theoretical exploration and case identification, document collection and review, as well as data processing and case study analysis. The first and second stages were obtained from review documents taken from Google Scholar and other eligible sources (Ministry of Health, National Coordination of Family Planning). Then the determinants of the stunting program objectives for family planning counselors were obtained by filtering documents using the PICOT (Population, Intervention, Comparison, Outcome, Time) model. The results of the PICOT selection show that 7 (n=7) of 29 (n=29) documents were selected with the main determinants of the stunting program being communication, information, education which includes fostering youth, prospective brides, families of toddlers, family companion teams, pregnant women, and collaboration with other health workers.